The sins of the fathers Germany, memory, method - Olick, Jeffrey K. (Chicago ; London : The University of Chicago Press, 2016)
National identity and political legitimacy always involve a delicate balance between remembering and forgetting. All nations have elements in their past that they would prefer to pass over the catalog of failures, injustices, and horrors committed in the name of nations, if fully acknowledged, could create significant problems for a country trying to move on and take action in the present. Yet denial and forgetting carry costs as well. Nowhere has this precarious balance been more potent, or important, than in the Federal Republic of Germany, where the devastation and atrocities of two world wars have weighed heavily in virtually every moment and aspect of political life. The Sins of the Fathers confronts that difficulty head-on, exploring the variety of ways that Germany's leaders since 1949 have attempted to meet this challenge, with a particular focus on how those approaches have changed over time. Jeffrey K. Olick asserts that other nations are looking to Germany as an example of how a society can confront a dark past casting Germany as our model of difficult collective memory